Unusual irradiation-induced disordering in Cu3Au near the critical temperature: An in situ study using electron diffraction. Issue 22 (20th September 2018) - Lear, Calvin Robert; Averback, Robert S.; Bellon, Pascal; Sand, Andrea E.; Kirk, Marquis A.
Abstract: Abstract : Atomic mixing by replacement collision sequences and other cascade effects is well known to create chemical disorder in irradiated alloys. Most studies of irradiation-induced disordering have focused on ex situ analysis of irradiated samples; however, fast in situ techniques are necessary to measure disordering at elevated temperatures without significant interference from concurrent re-ordering processes. In the present work, we use in situ electron diffraction with high speed data collection to measure the initial change in the long-range order parameter S with ion dose ϕ during 500 keV Ne + irradiation of Cu3 Au foils. The data reveal an unexpected and dramatic increase in the disordering rate as the critical order–disorder transition temperature T C is approached. Molecular dynamics simulations show that this increase is not due to temperature-dependent cascade mixing. We attribute the enhanced disordering, instead, to coupling between point defect fluxes and the chemical state of order.